2014
DOI: 10.1177/0284185114559871
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of microvascular obstruction in hypertrophic obstructive cardiomyopathy after percutaneous transluminal septal myocardial ablation

Abstract: The location of MO identified by MRI may be related to the effectiveness of PTSMA at the short-term follow-up. The left-sided MO is related to complete improvement in clinical symptoms and pressure gradients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It has comparable procedural mortality and efficacy to surgical myectomy despite being complicated by a higher rate of complete heart block requiring a permanent pacemaker [1][2][3]. To improve efficacy and decrease the risk of complete heart block, it is of paramount importance to detect a target vessel that exclusively supplies the basal left interventricular septum (BLS) and to limit the amount of ethanol injected [4,5]. Failure to locate such a target vessel leads to an unsatisfactory procedural result or abortion of the procedure [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has comparable procedural mortality and efficacy to surgical myectomy despite being complicated by a higher rate of complete heart block requiring a permanent pacemaker [1][2][3]. To improve efficacy and decrease the risk of complete heart block, it is of paramount importance to detect a target vessel that exclusively supplies the basal left interventricular septum (BLS) and to limit the amount of ethanol injected [4,5]. Failure to locate such a target vessel leads to an unsatisfactory procedural result or abortion of the procedure [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…To improve efficacy and decrease the risk of complete heart block, it is of paramount importance to detect a target vessel that exclusively supplies the basal left interventricular septum (BLS) and to limit the amount of ethanol injected [4,5]. Failure to locate such a target vessel leads to an unsatisfactory procedural result or abortion of the procedure [2,4]. One of the reasons for this failure is due to the difficulty of injecting ethanol into a small septal branch that is bifurcating at a steep angle.…”
Section: Introductionmentioning
confidence: 99%
“…Any fluid injected will therefore preferentially run towards the right side of the septum. The RV septum is a common site for undesirable infarction59 (figure 2). Right bundle branch block is reported in up to 60% of patients following ASA and may represent an underestimate 55 60–62.…”
Section: Results Following Asamentioning
confidence: 99%
“…Previous studies have demonstrated a significant relationship of the location of MVO or MI to the effectiveness of ASA. 8,24 Fourth, the use of the parallel imaging technique and phased-array coil affected the estimate of the myocardial signals. 25 The imaging planes differed between LGE and ceSSFP.…”
Section: Discussionmentioning
confidence: 99%